PENGARUH BIAYA KUALITAS TERHADAP TINGKAT PROFITABILITAS PADA CV. ANUGERAH ALAM NUSANTARA KABUPATEN BANTAENG - Muchriana Muchram; Andi Arman; Nurhayati Nurhayati (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2019)
This study aims to determine the effect of quality costs on profitability at CV. Anugerah Alam Nusantara Bantaeng Regency.The research method used is descriptive method using descriptive analysis method that explains data on the use of quality costs and used Net Profit Margin (NPM) as a benchmark of company profitability. Processed data is the result of the compony’s financial statements CV. Anugerah Alam Nusantara Bantaeng Regency. The results of this study indicate thet profitability is not much influenced by the amount of overall costs CV. Anugerah Alam Nusantara district.